2011
DOI: 10.1210/jc.2011-0569
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis and Renal Calcifications in Primary Hyperparathyroidism

Abstract: All patients with a diagnosis of PHPT should initially be evaluated for renal calcifications by unenhanced helical computed tomography. If calcifications are present, parathyroidectomy is recommended. If symptoms develop after parathyroidectomy, patients should be evaluated and treated similar to other patients with renal stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
97
0
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(123 citation statements)
references
References 67 publications
(84 reference statements)
8
97
0
18
Order By: Relevance
“…In spite of increased renal reabsorption of calcium, hypercalciuria is produced from the excess calcium load. Thus, one may find hypercalciuria in all patients with untreated HPT, and place all patients at an increased risk of renal calculi (19,20). In the present study, there was a positive correlation between PTH levels and urinary calcium level which is in agreement with the previous studies (21).…”
Section: Discussionsupporting
confidence: 93%
“…In spite of increased renal reabsorption of calcium, hypercalciuria is produced from the excess calcium load. Thus, one may find hypercalciuria in all patients with untreated HPT, and place all patients at an increased risk of renal calculi (19,20). In the present study, there was a positive correlation between PTH levels and urinary calcium level which is in agreement with the previous studies (21).…”
Section: Discussionsupporting
confidence: 93%
“…11,12 In addition, there are mixed results from studies that have tried to demonstrate that hypercalciuria itself promotes nephrolithiasis. 13 Given this information, the guidelines for the management of asymptomatic PHPT have recently changed. A 24-hour urine calcium is still recommended in the initial evaluation of suspected patients with PHPT, in order to differentiate it from FHH, but is no longer recommended as a criterion for parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may promote precipitation of crystals: increased renal calcium excretion and increased urine phosphate, increased urine oxalate, increased urine sodium, decreased urine citrate concentrations and proteinuria. Hypercalciuria is the main risk factor for kidney stone development in PHPT patients (8). Evidence, not confirmed by other studies, also suggested that relative high urine oxalate excretion and low urine citrate levels contribute to kidney stone risk in PHPT patients (3), while the role of urine phosphate, magnesium, sodium and potassium has not been established (8).…”
Section: Kidney Stones In Phpt Patientsmentioning
confidence: 99%
“…Hypercalciuria is the main risk factor for kidney stone development in PHPT patients (8). Evidence, not confirmed by other studies, also suggested that relative high urine oxalate excretion and low urine citrate levels contribute to kidney stone risk in PHPT patients (3), while the role of urine phosphate, magnesium, sodium and potassium has not been established (8). Therefore, recent guidelines (9, 10) suggested determining the risk of kidney stones in PHPT patients with 24-h urine calcium >400 mg by evaluating the urinary stone risk profile.…”
Section: Kidney Stones In Phpt Patientsmentioning
confidence: 99%